Effects of acupuncture for relieving preoperative anxiety in adolescents: A protocol for systematic review and meta-analysis. Issue 51 (23rd December 2021) - Yu, Ziru; Xian, Jin; Sun, Mi; Zhang, Wenxiu; Li, Linwei; Zhang, Xin; Yu, Huijuan
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Preoperative anxiety is a frequent burden affecting adolescent patients before various surgical procedures. Acupuncture has shown promise for addressing symptoms of preoperative anxiety in adolescents. This study is designed to evaluate the effectiveness of acupuncture for preoperative anxiety in adolescents. Methods: We will search the relevant randomized controlled trials by the following databases: PubMed, the Cochrane Central Register of Controlled Trials, EMBASE, China National Knowledge Infrastructure, Wan Fang, VIP, China Biomedical Literature Database, and TCM Literature Analysis and Retrieval Database. The process of selecting studies, extracting data and evaluating methodological quality will be conducted by 2 researchers independently. We will use Cochrane risk of bias tool for randomized trials to assess the risk of bias of included studies. Statistical analyses will be performed using R (version3.6.3). Ethics and dissemination: No patient's privacy are involved in this study, ethical approval will not be required. Our research results are intended to be published through conference reports and peer-reviewed journals. INPLASY registration number: INPLASY2021110096